2020
DOI: 10.1038/s41598-019-57263-4
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air formaldehyde (HCHO) pollution of urban coach cabins

Abstract: Urban coach cabin is an important indoor environment for long journey, formaldehyde (HcHo) is a carcinogenic gas and damages indoor air quality of cabins. in order to control the HcHo pollution, the air samples inside cabins were analysed with a thermally desorbed gas chromatograph, and the HcHo diffusion was simulated with a methodology of computational fluid dynamics (CFD). Results show that through the experimental monitoring, the HCHO pollution level range from 33.6 to 142.3 μg/m 3 , decrease quickly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Notably, as individuals often remain indoors longer than outdoors, HCHO pollution indoors must be reduced to avoid potential detrimental effects on human health. Vehicle cabins have been recognized as important indoor environments, and recent reports have shown that the indoor air quality of vehicle cabins is easily polluted by various VOCs (such as toluene) and HCHO 45–47 . Individuals should thus increase the rate of indoor ventilation and cabin, particularly after introducing new sources of HCHO inside, and decrease HCHO pollution indoors or in cabins.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, as individuals often remain indoors longer than outdoors, HCHO pollution indoors must be reduced to avoid potential detrimental effects on human health. Vehicle cabins have been recognized as important indoor environments, and recent reports have shown that the indoor air quality of vehicle cabins is easily polluted by various VOCs (such as toluene) and HCHO 45–47 . Individuals should thus increase the rate of indoor ventilation and cabin, particularly after introducing new sources of HCHO inside, and decrease HCHO pollution indoors or in cabins.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al [18] recommended the optimal deflect angle for tunnel ventilation using CFD. Qin et al [19] recommended the numerical simulation of airborne HCHO pollution in vehicle cabins using CFD. Through CFD simulation, it can be an accurate prediction of air pollution flow properties and species transport [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For the experiments in this work, the instrument was placed in an air-conditioned sea container next to the chamber. Parts of the instrument were temperature stabilized: the stripping coil at 283 K, the reaction volume at 341 K and the fluorimeter at 308 K. This ensured that the reaction efficiency and fluorescence detection sensitivity remained approximately constant (Rurack and Spieles, 2011;Resch-Genger and Rurack, 2013). The tubing of the peristaltic pumps was exchanged every 2 weeks due to tube degradation and in order to prevent occlusions or a major loss of pumping performance, which could cause the instrument sensitivity to change by up to 10 % within this time span (Sect.…”
Section: Hcho Detection By the Wet-chemical Methods Using The Hantzsch Reactionmentioning
confidence: 99%
“…Formaldehyde (HCHO) is a pollutant that is present in ambient air but also indoors. It affects human health by irritating the respiratory system and by being carcinogenic (Gupta et al, 1982;Casset et al, 2005;World Health Organization, 2010;Fortems-Cheiney et al, 2012;Liu et al, 2015;Salthammer, 2019;Qin et al, 2020). It is formed in the atmosphere as a product of the oxidation of volatile organic compounds (VOCs) and in combustion processes, includ-ing biomass burning.…”
Section: Introductionmentioning
confidence: 99%